Secondary Lymphoid Organs in Mesenchymal Stromal Cell Therapy: More Than Just a Filter - Zheng, Di; Bhuvan, Tejasvini; Payne, Natalie L.; Heng, Tracy S. P. (Frontiers in Immunology, 2022)
Mesenchymal stromal cells (MSCs) have demonstrated therapeutic potential in inflammatory models of human disease. However, clinical translation has fallen short of expectations, with many trials failing to meet primary endpoints. Failure to fully understand their mechanisms of action is a key factor contributing to the lack of successful commercialisation. Indeed, it remains unclear how the long-ranging immunomodulatory effects of MSCs can be attributed to their secretome, when MSCs undergo apoptosis in the lung shortly after intravenous infusion. Their apoptotic fate suggests that efficacy is not based solely on their viable properties, but also on the immune response to dying MSCs. The secondary lymphoid organs (SLOs) orchestrate immune responses and play a key role in immune regulation. In this review, we will discuss how apoptotic cells can modify immune responses and highlight the importance of MSC-immune cell interactions in SLOs for therapeutic outcomes.